Completeness of Medical Record Files and The Timeliness of BPJS Claims on Inpatients with Bronchitis at Islamic Hospital Purwokerto - Putri Sepna Regina; Harry Fauzi (Proceedings Series on Health & Medical Sciences, 2026)
Background: One of the crucial determinants of the quality of medical services provided by hospitals is the availability of adequate and complete data or information concerning medical records, which significantly impacts the submission of BPJS claims. Method: This research utilizes a quantitative approach with a descriptive research design, employing a cross-sectional data collection method. Results: The completeness of medical records for inpatients with bronchitis, categorized into indicators such as Participant Eligibility Letter (SEP), supporting examinations, the accuracy of codes, and inpatient billing resumes, was complete for 75 (100%) cases. Medical summaries were categorized as complete for 34 (45.33%) cases and incomplete for 41 (54.67%) cases. The indicator of inpatient admission orders was complete for 6 (8%) cases and incomplete for 69 (92%) cases. The timeliness of BPJS inpatient claims was categorized as timely for 49 (65.33%) cases and untimely for 26 (34.67%) cases. Conclusion: The completeness of medical records significantly affects the timeliness of BPJS claims, where incomplete documentation, particularly in medical resumes and inpatient admission orders, contributes to delays in claim submission.